Factors of Language Shift in Sumbawanese at South Anjani 1: A Sociolinguistic Study - Nurhidayatul Aini; Mahyuni Mahyuni; Lalu Ali Wardana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2021)
This study was aimed at finding out the language dominance and language shift factors that influence the shift from Sumbawanese to Indonesian and Sasak. The Sumbawanese refers to Taliwang dialect which is the native language of the Sumbawa community at South Anjani 1. The study was conducted in South Anjani 1, East Lombok. The subjects and informants of the study were teenagers, the parents, and the chief of the village. The subjects of study were teenagers so that it be worthwhile to predict the future of the vernacular. The study used qualitative research method in collecting and analyzing the data. The instruments of data collection were observation, interview, and recording. After collecting the data, it was analyzed by the following stages, transcription, identification, and classification. The findings show that the dominant language used by teenagers in South Anjani 1 is Indonesian. This appears to the affection of language shift of their native language, Sumbawanese. The language shift is caused by some factors, social, economic, political, demographic, attitudes and values, family, and education factors.